Census of “ Microturbellarians” (free-living Platyhelminthes) of the zoogeographical regions originating from Gondwana - Noreña, Carolina; Brusa, Francisco; Faubel, Anno (Zootaxa, 2003)
In this study we review microturbellarian species known to occur in zoogeographical regions that originated from Gondwana. The 510 reported species are from all types of aquatic environments (marine, brackish and freshwater). Complete data of the distribution and bibliographical references are provided. In addition, taxonomic discrepancies, as well as new combinations, are clarified. This checklist is the first revised compendium of the microturbellarians of the Gondwanian zoogeographical regions.